Mapeamento preliminar de áreas urbanas de inundação - Suleiman, Hélio César (2004)
Nowadays, the quest for solutions to urban problems that affect population quality of life cannot ignore the concepts of inundation and flood in urban areas, which are frequently seen in a number of cities within the country and, whenever reaching crowded areas, bring considerable damage that is, on its turn, irreparable due to the loss of human lives. The proposed methodology was reached with the objective of providing a computational tool to outline areas with higher or lower risk of flood for planning a draining system and urban use. The hydrodynamic propagation model has been developed by using the MacCormack explicit scheme, making it possible to be applied to urban channels. In the case of inundations, corresponding plates and sections are recorded for further generating the inundation preliminary map with the aid of a topographic software. Tests focused on hydrodynamic propagation in a real channel, stream of the Retiro Saudoso, in the city of Ribeirão Preto, state of São Paulo, having a map representing a estimative flooding area. The final outcome of this work might be used as part of a decision-making support system for authorities to estimate and to map flood along a channel.